1997
DOI: 10.1109/86.650279
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic weight acceptance mechanics in transtibial amputees wearing the Single Axis, Seattle Lite, and Flex Foot

Abstract: Loading response challenges the limb with the dual demands of accepting rapidly moving body weight to both absorb the shock of floor contact and create a stable limb over which the body can advance. Delay in achieving foot flat contact with the floor causes a prolonged period of heel only support and results in an unstable base of support for those persons with transtibial amputations. The purpose of this study was to identify mechanical causes of instability during weight acceptance with three different prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 15 publications
1
75
0
1
Order By: Relevance
“…The persons with bilateral transtibial amputations in this study walked with less peak-to-peak stance-phase knee flexion than the nondisabled individuals walking at similar speeds. Other studies have reported decreased stance-phase knee flexion in persons with unilateral transtibial amputations [12,23]. The subjects with amputations may have attempted to reduce stance-phase knee flexion to minimize relative motion between the residual limb and the prosthetic socket and to avoid high, uncomfortable pressures by maintaining the GRF vector orientation nearly coincident with the longitudinal axis of their residual limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The persons with bilateral transtibial amputations in this study walked with less peak-to-peak stance-phase knee flexion than the nondisabled individuals walking at similar speeds. Other studies have reported decreased stance-phase knee flexion in persons with unilateral transtibial amputations [12,23]. The subjects with amputations may have attempted to reduce stance-phase knee flexion to minimize relative motion between the residual limb and the prosthetic socket and to avoid high, uncomfortable pressures by maintaining the GRF vector orientation nearly coincident with the longitudinal axis of their residual limb.…”
Section: Discussionmentioning
confidence: 99%
“…The inferior walking performance of persons with amputations is often attributed to the current state of prosthetic technology [11][12]14,[16][17]]. This conclusion is based on gait studies of persons with unilateral transtibial amputations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gait of a person with an amputation, the prosthetic joint amplitude is typically lower than in the gait of a nondisabled person [18][19]. Therefore, 15° of dorsiflexion is a reasonable target [20]. We did not consider the moment from the horizontal component of the ground reaction force because it would only decrease the value of M(α) as calculated in Equation 1, but we used the conservative approach to estimate the needed stress for …”
Section: (4)mentioning
confidence: 99%
“…While it is known that persons with lower limb amputations have slower self-selected walking speeds [16][17][18], increased nonprosthetic side leg loading [19], and decreased gait symmetry [19][20][21][22][23] compared to persons with no physical impairments, typical, unimpaired gait data were used in calculating the roll-over shape of the prototype in this study. Typical loading is often assumed in measuring the roll-over shape of prosthetic feet through mechanical testing [5,9,24].…”
Section: Biomechanical Gait Datamentioning
confidence: 99%